Effect of Cooking on Cooking Time, Nutritional Content and Sensory Properties of Pawpaw-treated Bambara Groundnut (International Journal of Technology and Management Research, 2020)
Cooking of bambara groundnut is time and energy consuming. This research was therefore carried out to find a way of reducing the cooking time of bambara groundnut and at the same time reduce losses of nutrients. Green pawpaw slices, both fresh and dried were added to the raw bambara groundnut and cooked. The treated Bambara groundnut recorded the lowest cooking time (P